IMPLEMENTAÇÃO DA AGENDA 21 ESCOLAR EM FERNANDES PINHEIRO/PR:EDUCAÇÃO AMBIENTAL PARA TERRITORIALIDADE? - Silva, Ian Navarro de Oliveira (2011)
This research aims to check the influence of implementation of the program “Building the school Agenda 21” in the conceptions and practices of environmental education of teachers in state schools in the municipality of Fernandes Pinheiro/PR between the years of 2005 and 2009, and how they reflect in the exercise of territoriality of the students. Although accepted by consensus, environmental education has multiple theoretical and methodological conceptions resulting from political and economic interests of social groups related to them. The School Agenda 21 requires discussion in schools of the environmental issue with a view to the understanding through environmental education. Understanding how environmental education programs are constructed in schools, as they are perceived and developed by teachers and which are the results for the students, can contribute to the improvement and effectiveness of these programs and to the understanding and overcoming the environmental issue. Is this research, deductive, they were used as techniques the documentary and bibliographic research, to prepare the theoretical reference and analysis and discussion of results, and standardized interviews with teachers of schools for data collection, qualitative, treaty of through content analysis, about their views and environmental education practices, as well as the desired results and the ones already reached with students. The obtained results allow us to identify characteristics of the construction processes of School Agenda 21 and teachers training in environmental education, which reflect in their conceptions and practices and also in the exercise of territoriality of the students.